The Influence of Social Media Marketing on Apparel Brands’ Customers’ Satisfaction: The Mediation of Perceived Value - Yang, Yongzhong; Khan, Zobi; Zhang, Yu (Asian Academy of Management Journal, 2020)
The development of social media has changed traditional media by providing a platform to conduct marketing and advertising activities. Nowadays, social media offers the opportunity to build a relationship between customers and brands. The strategic use of social media marketing has significant importance for customers as well as for marketers. In this paper, the influence of social media marketing activities (SMMAs) is assessed on apparel brands’ perceived value and Chinese customers’ satisfaction. The data was collected through a quantitative survey-based approach from Chinese social media and apparel brands’ users (n = 355). The collected data from respondents were analysed through the confirmatory factor analysis (CFA) and Hayes PROCESS macro. Based on our findings, it is noted that SMMAs play an essential role in improving the brand perceived value and customers’ satisfaction in China. Moreover, it is also concluded that the apparel brand’s perceived value significantly mediates the relationship between SMMAs and customers’ satisfaction. This study provides several theoretical and practical guidelines to the marketers in China to effectively implement their advertising activities on social media platforms.